(3JaSjQ CHj GdSYhOs - (3eLghds
(3ChdgG (B:s
(3Pdc Hbhdc(B: (3SYjJ aj MGLI adGf hjLH Cf CSYi hCfJ NHjQ HCf TCf GdLed Jchf eDcOI deVehf GdUOQs
(3BNQgG (B:s
(3bGd QH Efj bJdJ efge faSG Cf jbJdhf HebGHdJgG hCNj gGQhf gh CaUM efj dSGfG aCQSdg eYj QOAG Cj eYjfG hgh aj GdCUd GSes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc TQja eUWai, SfI?s
Keywords: (3GdJaSjQ hYdhe GdbQBfs